Electronic Commerce in Small to Medium-Sized Enterprises 2004
DOI: 10.4018/978-1-59140-146-9.ch019
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Risk Factors of Moving to a Remote Application Outsourcing Model

Abstract: In the last few years there has been much interest in the delivery of software-as-a-service. The concept of remote application outsourcing, or application service provision (ASP), has emerged as a solution aiming to offer organizations, mainly small to medium-sized enterprises (SMEs), access to key applications that were previously unaffordable. This chapter examines this model of software delivery, focusing on the potential risks that could be associated with it. The authors identify shared risks with traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…As a result, alliances could be seen as a particularly important solution for having access to these competencies (Hagedoorn, 1993;Singh, 1997). To further support this idea, the dynamics of the ASP market Weerakkody, Tebboune, Currie et al, 2003) should also be taken into consideration; as McKenna (1985) previously suggested, strategic alliances are found to be a particularly suitable strategic option in fast-changing industries in order to compete effectively, and to share the costs of developing new technologies.…”
Section: Threat Of New Entrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, alliances could be seen as a particularly important solution for having access to these competencies (Hagedoorn, 1993;Singh, 1997). To further support this idea, the dynamics of the ASP market Weerakkody, Tebboune, Currie et al, 2003) should also be taken into consideration; as McKenna (1985) previously suggested, strategic alliances are found to be a particularly suitable strategic option in fast-changing industries in order to compete effectively, and to share the costs of developing new technologies.…”
Section: Threat Of New Entrantsmentioning
confidence: 99%
“…It should, also, be noticed that due to the lack of experience with the ASP model -as it is still developing -potential ASPs and their partners might still be unsure of the overall conception of the ASP model. Moreover, due to the dynamic character of the ASP model (Tebboune et al, 2003;Weerakkody et al, 2003), the understanding of the components of the ASP model is altered continuously, adding, thus, to the difficulty of identifying the required elements. As a result, potential ASPs are constantly facing the challenge of finding an appropriate way of designing their business model, including determining the value-added components necessary for differentiating their offerings.…”
Section: Strategic Alliances As a Processmentioning
confidence: 99%